2014
DOI: 10.1038/ncomms6375
|View full text |Cite
|
Sign up to set email alerts
|

Omega-1 knockdown in Schistosoma mansoni eggs by lentivirus transduction reduces granuloma size in vivo

Abstract: Schistosomiasis, one of the most important neglected tropical diseases worldwide, is caused by flatworms (blood flukes or schistosomes) that live in the bloodstream of humans. The hepatointestinal form of this debilitating disease results from a chronic infection with Schistosoma mansoni or Schistosoma japonicum. No vaccine is available to prevent schistosomiasis, and treatment relies predominantly on the use of a single drug, praziquantel. In spite of considerable research effort over the years, very little i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 63 publications
4
63
0
Order By: Relevance
“…A long-established model of the schistosome egg granuloma employs tail vein injection of eggs into mice, which leads to formation of circumoval granuloma in the mouse lung (56-58). The latter approach has been extensively employed for immunopathogenesis-related studies of ω1 (16). Accordingly, to elicit circumoval granulomas, ∼3,000 WT or Δω1 LE were injected into the lateral vein of the tail of BALB/c mice.…”
Section: Resultsmentioning
confidence: 99%
“…A long-established model of the schistosome egg granuloma employs tail vein injection of eggs into mice, which leads to formation of circumoval granuloma in the mouse lung (56-58). The latter approach has been extensively employed for immunopathogenesis-related studies of ω1 (16). Accordingly, to elicit circumoval granulomas, ∼3,000 WT or Δω1 LE were injected into the lateral vein of the tail of BALB/c mice.…”
Section: Resultsmentioning
confidence: 99%
“…# P < 0.05, vs the group of T2 RNase and TGF-β1 co-treatment (rT2 + TGF-β1+) potent Th2 polarization of CD4+ T cells during infection, due to its RNase activity and glycosylation (Everts et al 2009;Steinfelder et al 2009). Hagen et al (2014) have demonstrated that knockdown of Omega-1 in S. mansoni eggs could lead to a significant decrease in the size and cellular composition of granulomas. However, these findings have not established whether Omega-1 and other T2 RNase family members from schistosomes play a direct role in activation of HSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Omega-1 can drive Th2 responses in dendritic cells and its cytotoxicity appears to control granuloma size [36]. Eggs from Trichuris suis (T. suis) have been tested as potential therapeutic agents against experimental and clinical inflammatory bowel disease (IBD) [37,38], but the responsible factors have not been elucdiated.…”
Section: Eggs and Soluble Egg Extracts (Sea)mentioning
confidence: 99%